Diversity and Diversity Management in Education A European Perspective - Quaiser-Pohl, Claudia 1965- (Waxmann Verlag GmbH, 2013)
Globalisation and efforts for equality nowadays go together with the debate on differences and diversity within countries, societies and organisations. Thus "diversity" and "diversity management" have become very popular topics in educational research and policy all over Europe. This book is the documentation of an international workshop of researchers from Poland, Germany and France. It combines articles on "diversity" from different disciplines. With its interdisciplinary and international, i.e. European, perspective, it leads to a better understanding of the phenomenon. It can improve the "diversity competence" in research and training and is particularly appropriate for international study programmes
Keywords: Differenzierung; Heterogenität; Pädagogikstudium; Bildungswesen; Frankreich; Deutschland; Polen; Konferenzschrift -- 2011 -- Koblenz